Digital Transformation in Islamic Religious Education: Trend or Necessity in the Post-Pandemic Era - Azizeh Mukarromah; Abu Hasan Agus R; Umar Manshur (Indonesian Journal of Education and Social Studies, 2025)
The rapid digital transformation following the COVID-19 pandemic has reshaped the landscape of Islamic Religious Education (PAI), creating both opportunities and challenges in teaching religious values. This study aims to examine whether digitalization in PAI serves merely as a temporary adaptation or as a sustainable pedagogical strategy for value-based education. Using a qualitative case study approach, data were collected from two Islamic educational institutions: one elementary school and one secondary school. This was achieved through in-depth interviews, classroom observations, and documentation of digital learning materials. The findings reveal that teachers’ low digital literacy significantly hinders the effective integration of technology, while digital media use has improved learning flexibility, accessibility, and engagement. Furthermore, digitalization has transformed teaching methods, encouraging more reflective and contextual approaches to Islamic values education. The study presents new empirical evidence on how digital transformation influences pedagogical practices, underscoring the necessity for ongoing teacher training and institutional policy support to foster meaningful and sustainable innovation in religious education.